AVAILABILITY OF AES DEVELOPMENT FOR THEORETICAL EDUCATION OF CIVIL AVIATION PERSONNEL - P. A. Kolokolnikov; S. N. Yablonskiy (Научный вестник МГТУ ГА, 2016)
The article is devoted to the automated educational systems as means of theoretical education of civil aircraft personnel. The author considers different types of AES, handles the problem of actuality of such systems today and of the necessity of their development and possible availability.